Salmonella hvittingfoss, a rare case of postoperative endometritis: A case report and review of the literature - Sarah Baïli; Sascha Vereeck; Yves Jacquemyn (Clinical Case Reports, 2024)
Key clinical message Microbiological diagnosis of endometritis and appropriate antibiotic treatment based on the antibiogram is essential. We should remain critical about the potential etiologic pathogens, especially when traveling abroad and during pregnancy. Therefore, it is essential to obtain cultures prior to the administration of antibiotics. Abstract We present a case of postoperative endometritis in a patient with incomplete miscarriage, who underwent dilatation and curettage. Blood, cervical and stool cultures revealed the presence of Salmonella hvittingfoss. Gynecological postoperative infections with Salmonella spp. are rare according to the current literature.